Effectiveness of Development of Perceptive Skills Directed to Increase the Social Activity of Students in Future Teachers (Eurasian Scientific Herald, 2022)
In this article, the content of forming social activity based on the formation of basic competencies in students, the ability to eliminate conflicts and problems that have arisen as a component of social activity will help students to occupy a worthy place in the micro-society in the future, Important components of social activity, which are not always manifested in the students' activities, but can be felt through their actions, are analyzed.